2012
DOI: 10.1016/j.breast.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Post-mastectomy pain syndrome: Incidence and risks

Abstract: One hundred seventy-four women were examined. The mean age was 58 years. The incidence of pain syndrome was 52%. Younger women (<40 years) and those who were submitted to axillary lymph node dissection (with more than 15 lymph nodes excised) have shown a significantly increased risk of pain syndrome after surgery for breast cancer (relative risk (RR) =5.23 95% confidence interval (CI): 1.11-24.64) and (RR=2.01 95% CI: 1.08-3.75).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 16 publications
11
77
2
5
Order By: Relevance
“…The presence of pain in this study had higher frequency than in the studies found in the literature, for which rates ranged from 22% to 55% [20][21][22][23] . The findings of this research reveal the high prevalence of chronic pain, but there was no statistically significant difference between the groups.…”
Section: Discussioncontrasting
confidence: 68%
“…The presence of pain in this study had higher frequency than in the studies found in the literature, for which rates ranged from 22% to 55% [20][21][22][23] . The findings of this research reveal the high prevalence of chronic pain, but there was no statistically significant difference between the groups.…”
Section: Discussioncontrasting
confidence: 68%
“…Persistent postsurgical pain was reported at least 3 months after breast cancer surgery (range 3.28-72.50 mo) in all eligible studies. Seven studies reported that other causes of persistent pain had been excluded, 32,37,38,42,44,46,52 but only 1 study explicitly used the IASP criteria for defining persistent postsurgical pain. 44 The median sample size was 416 (IQR 250-772), and the median duration of follow-up was 24 months (IQR 12-42 mo) (Appendix 7, available at www.…”
Section: Resultsmentioning
confidence: 99%
“…Persistent post-surgical pain lasting over 3 months is a common complication following breast surgery [162], with a reported incidence between 20% and 68% [163][164][165][166]. The variance may be attributed to multiple factors, including differences in definition and the type of breast cancer surgery treatment involved.…”
Section: Persistent Post-surgical (Chronic) Painmentioning
confidence: 99%
“…[5] The pain itself, mostly neuropathic in nature, is often described as burning, shooting, pressure, numbness, or phantom [162,[165][166][167]; and is described as "severe" in 10% of patients [8,168]. Reported to occur in the axilla, chest wall and proximal medial arm or shoulder [53, 162,169,170], the pain may extend beyond the area of the mastectomy, and is strongly correlated with depression and anxiety [171].…”
Section: Persistent Post-surgical (Chronic) Painmentioning
confidence: 99%